Semisynthetic blasticidin S ester derivatives show enhanced antibiotic activity. Issue 4 (17th March 2023) - Gannett, Cole; Banks, Paige; Chuong, Christina; Weger-Lucarelli, James; Mevers, Emily; Lowell, Andrew N.
Abstract : A potential rich source of new antimicrobials is undeveloped natural product cytotoxins. We used semisynthesis to derivatize the neglected antibiotic blasticidin S, creating ester derivatives with enhanced selectivity for bacteria. Abstract : A rich potential source of new antibiotics are undeveloped natural product cytotoxins, provided they can be derivatized to restrict their activity to bacteria. In this work, we describe modification of one such candidate, the broad-spectrum, translation termination inhibitor, blasticidin S. By semisynthetically modifying blasticidin S, we produced a series of ester derivatives of this highly polar, zwitterionic compound in a single step. These derivatives showed a marked increase in activity against Gram-positive bacteria and an increase in selectivity index for pathogenic bacteria over human cells. The results of this study suggest that semisynthetic derivatization of blasticidin S and other neglected natural product antimicrobials has the potential to increase their activity against and selectivity for bacteria, an approach that can be leveraged for the development of leads against antimicrobial resistant pathogens.